1980
DOI: 10.1093/jn/110.10.2058
|View full text |Cite
|
Sign up to set email alerts
|

Growth Depression in Taurine-Depleted Infant Monkeys

Abstract: In order to determine the effect of taurine depletion in primates, two species were selected which differed in their taurine conjugtion of bile acids. Consequently, eight cebus (taurine conjugators) and nine cynomolgus monkeys (glycine conjugators) were raised from birth with soybean infant milk formula lacking taurine. Half the monkeys received a 500 ppm taurine supplement. After 5 months the taurine concentration of plasma, urine and several tissues was greatly reduced in the unsupplemented monkeys. The leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(30 citation statements)
references
References 16 publications
0
30
0
Order By: Relevance
“…An animal study has indicated that taurine may be important for the growth of monkeys [6]. Hayes et al [5] have reported retinal degeneration associ ated wiih taurine deficiency in kittens.…”
Section: Discussionmentioning
confidence: 99%
“…An animal study has indicated that taurine may be important for the growth of monkeys [6]. Hayes et al [5] have reported retinal degeneration associ ated wiih taurine deficiency in kittens.…”
Section: Discussionmentioning
confidence: 99%
“…Two species of infant primates (cebus and cynomolgus) were shown to depend on a dietary source of taurine ,for maximum growth measured by weight gain (40). However, these observations remain unexplained since dietary intake and absorption were not examined.…”
Section: Discussionmentioning
confidence: 99%
“…Recently there has been considerable interest in tau rine as a nutritionally important and perhaps essential compound [2,3,8,15,48,50,66]. It is clearly an essen tial nutrient for the cat and kitten, and its deficiency results in a number of neurological disorders, including visual dysfunction, retinal and tapetal degenerations, and impairment of normal cerebellar and visual cortex development [14,20,34,35,44,53,[56][57][58].…”
Section: Introductionmentioning
confidence: 99%